Comparison of genotoxic impurities in extracted nicotine vs. synthetic nicotine - Nisathar, Ayesha; Chen, Hui; Lei, Xiaoli; Zeng, Zeyu; Chen, Jia (Frontiers in Chemistry, 2024)
Nicotine is a chiral alkaloid; nitrogen-containing organic compound that occurs naturally. (S)-nicotine is extracted from Tobacco plants and used as the key addictive ingredient in many smoking products. Synthetic nicotine has gained the interest of many smoking product manufacturers over the last few decades due to the ease and low cost of manufacturing. Another claimed advantage of synthetic nicotine is the absence of genotoxic impurities that form during the extraction process of nicotine. These impurities are other plant alkaloids, phenolic compounds, and heavy metals. Additionally, the U. S. FDA has implemented new regulations on the quality control of synthetic nicotine. However, only a very few research articles have been published on assessing the complete impurity profile of synthetic nicotine. Therefore, the need to know the composition difference between tobacco-extracted nicotine vs. synthetic nicotine is highly necessary. In this research study, the impurity profile of thirteen different lots of synthetic nicotine was compared with fourteen lots of nicotine extracted from plants using in-house analytical methods. First, the samples were tested for other alkaloids and phenols by reversed-phase High-Performance Liquid Chromatography (HPLC). Second, the chiral purity was analyzed by normal phase HPLC. Third, lead and arsenic content were tested by atomic absorption and fluorescence spectrometry. Fourth, nicotine-specific nitrosamines were tested by LC-MS. The reversed phase HPLC data suggested similar quantities of total impurities in both synthetic and tobacco-extracted nicotine (0.1%). However, synthetic nicotine lacks some impurities such as cotinine, nornicotine, and nicotine-N-oxide. Additionally, the synthetic nicotine lots used in this study have high enantiomeric purity similar to the tobacco-extracted nicotine.